A SECONDARY SCHOOL STUDENT’S CRITICAL THINKING ABILITY PROFILE IN NATURAL SCIENCE SUBJECT MATTERS BASED ON LEARNING STYLE - Nur Afdila; Septi Budi Sartika (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This research aims to describe students' critical thinking ability in science subjects based on learning style. The research method uses qualitative research with phenomenological approaches. The research site was conducted at SMP Muhammadiyah 5 Tulangan Sidoarjo. Data retrieval techniques using tests, questionnaires, and interviews. Data analysis techniques using the Miles & Huberman (2014) model include data reduction, data presentation, verification and conclusions. There are 6 indicators of critical thinking abilities revealed that include interpretation, analysis, evaluation, inference, explanation, and self-regulation (Facione, 2013). The study only used 5 indicators of critical thinking ability without self-regulation, this is because they cannot be revealed in a short time. The results of the study found that (1) indicators achieved in visual learning styles include interpretation, evaluation, and inference, (2) indicators achieved in auditory learning styles namely interpretation, analysis, evaluation, and explanation, and (3) indicators achieved in kinesthetic learning styles namely: interpretation and evaluation. All subjects achieved not same indicators, while the all subjects also did not achieve all indicators of critical thinking ability. Further research is expected to be the efforts of natural science teachers in achieving all indicators of critical thinking ability, among others by doing habituation and consistent in training critical thinking ability.Keywords: Critical thinking ability,Secondary school student’s,Natural Science,Learning Style